Hexadecene compounds, synthesis methods and applications thereof
The synthesis of aza[7]spiroene compounds by electrochemical synthesis method has solved the problem of low efficiency of hole transport materials in perovskite solar cells in the prior art, and achieved an efficient energy conversion efficiency of 18.8%.
Patent Information
- Application Number
- CN202210955511.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-10
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-08-10
AI Technical Summary
In the prior art, Spiro-OMeTAD, a D-π-D type organic hole transport material used in perovskite solar cells, has problems such as complex chemical structure, long synthetic routes, expensive prices and low hole mobility, resulting in low energy conversion efficiency.
By electrochemical synthesis, the electrooxidation C-C, C-N coupling and aromatization were carried out in series by electrochemical synthesis using 6-amino groups as raw materials, and the target compound was obtained by alkylation reaction. This method avoids the use of catalysts and chemical oxidants, and has the advantages of high reaction selectivity, high synthesis efficiency and environmentally friendly.
The prepared aza[7]spiroene compound is used as a hole transport material to improve the energy conversion efficiency of perovskite solar cells. The experimental results show that the energy conversion efficiency can be as high as 18.8%.
Smart Images

Figure CN116332827B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of synthetic chemistry and solar cell materials, and specifically relates to Aza[7]helicene compounds, preparation methods and applications. Background Art
[0002] Helicene is a polycyclic aromatic hydrocarbon (PAH) compound formed by the ortho-fusion of multiple aromatic rings. It has a unique helical structure, and the stacking of molecules easily produces more intermolecular contacts. Introducing heteroatoms (N, O, S, B) into the helicene skeleton can increase the non-planarity, three-dimensional intermolecular / intramolecular interactions and unique optoelectronic properties of the helicene molecule. It can be used as an organic semiconductor in various fields such as organic light-emitting diodes (OLEDs), organic field-effect transistors (OFETs) and organic photovoltaics (OPVs).
[0003] The formation of CC and CN bonds is a key step in the bottom-up construction of PAHs and N-doped PAHs (aza-PAHs) with atomic precision. Most existing strategies and methods such as cyclopiextension (APEX), π-extended decarboxylation (PEDA), Scholl reaction, alkyne cyclization, aromatic trimerization, oxidative cyclization, transition metal cyclocatalyzed oxidative CH activation / cyclization require pre-functionalized substrates or even use stoichiometric amounts of toxic and waste-generating oxidants such as copper (II), silver (I) salts, dichlorodicyanoquinone (DDQ) and N-chlorosuccinimide (NCS). Electrochemical synthesis is a controllable and most direct integrated electrode preparation method with the advantages of being simple, rapid, clean, cheap and sustainable. At present, the direct electrochemical cyclization of aza-PAHs using readily available PAA as starting materials without catalysts is still rare.
[0004] Organic-inorganic hybrid perovskite solar cells (PSCs) have become one of the current research hotspots due to their excellent optoelectronic properties. In PSCs, hole transport materials (HTMs) avoid direct contact between the perovskite layer and the positive electrode of the battery during hole extraction and transport, reduce the recombination of electrons and holes, and improve the surface morphology of the perovskite layer. They are key components of PSCs devices. High-performance HTMs should have the following properties: (1) HOMO and LUMO energy levels that match the perovskite layer; (2) high hole mobility and conductivity; (3) low raw material cost, simple synthesis and preparation, and stable physical and chemical properties under conditions of high temperature, high light, and high humidity.
[0005] In the prior art, the most widely used D-π-D type organic hole transport material in perovskite solar cells is mainly 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD). However, Spiro-OMeTAD has a complex chemical structure, a long synthesis route, and is expensive. At the same time, the hole mobility of this material is low, resulting in low energy conversion efficiency of perovskite solar cells. It is usually necessary to use lithium bis(trifluoromethylsulfonyl imide) (LiTFSI), tert-butylpyridine (t-BP), etc. for p-type doping to increase the hole mobility, but this type of doping will lead to unstable performance of the battery device and expensive material costs. Reported Azabis[6]helicene compounds can be used as D-π-D type organic hole transport materials, but the key step in the synthesis of helicene is to use NCS, which has poor atom economy and low synthesis efficiency. Summary of the invention
[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a synthetic The invention discloses a preparation method of a 1,2-diaza[7]helicene compound and its application in hole transport materials and solar cells.
[0007] To achieve the above purpose, the technical solution specifically adopted by the present invention is as follows:
[0008] In a first aspect, the present invention provides a Aza[7]helicene compound, the structural formula of which is shown in Formula I or Formula II:
[0009]
[0010] Wherein: R is selected from a straight chain or branched C6-C16 hydrocarbon group.
[0011] In a second aspect, the present invention provides a synthetic The method for preparing aza[7]helicene compound is as follows:
[0012] 6-amino As a raw material, an electrochemical synthesis method is used to synthesize a compound represented by formula III, wherein formula III is as follows:
[0013]
[0014] As a preference for the second aspect above, the electrochemical synthesis method is a series reaction consisting of electro-oxidation CC, CN coupling and aromatization.
[0015] In a third aspect, the present invention provides a synthetic The method for preparing aza[7]helicene compound is as follows:
[0016] First, 6-amino As a raw material, an intermediate compound shown in formula III is synthesized by an electrochemical synthesis method, and then the intermediate compound is alkylated to obtain a compound shown in formula I Aza[7]helicene; wherein the compounds of formula III and formula I have the following structural formulas:
[0017]
[0018] Wherein: R is selected from a straight chain or branched C6-C16 hydrocarbon group.
[0019] As a preferred embodiment of the third aspect, the electrochemical synthesis method is a series reaction consisting of electro-oxidation CC, CN coupling and aromatization.
[0020] In a fourth aspect, the present invention provides a synthetic The method for preparing aza[7]helicene compound is as follows:
[0021] The amino group represented by formula VI The pyrazine fused compound shown in formula II was synthesized by electrochemical synthesis method. Aza[7]helicene compounds;
[0022]
[0023] Wherein: R is selected from a straight chain or branched C6-C16 hydrocarbon group.
[0024] As a preferred embodiment of the fourth aspect, the electrochemical synthesis method is a series reaction consisting of electro-oxidative CN coupling and aromatization.
[0025] As a common preference of the second, third and fourth aspects above, the specific implementation process of the electrochemical synthesis method is as follows: the raw material is placed in an electrolytic cell with an anode and a cathode, nBu4NPF6 or 1-butyl-3-methylimidazolium tetrafluoroborate is used as a supporting electrolyte, and an electrochemical reaction is carried out in an organic solvent at a constant potential of 1.0 to 3.0 V.
[0026] Furthermore, the electrolytic cell is preferably a single-cell electrolytic cell, the anode is preferably a Pt anode, the cathode is preferably a graphite cathode, and the organic solvent is preferably acetonitrile.
[0027] In a fifth aspect, the present invention provides a method as described in the first aspect above. Aza[7]helicene compound or a compound synthesized by any one of the methods of the second aspect, the third aspect and the fourth aspect Application of 1,1-diaza[7]helicene compounds as hole transport materials.
[0028] In a sixth aspect, the present invention provides a perovskite solar cell, wherein the hole transport layer material of the perovskite solar cell is the material described in the first aspect above. Aza[7]helicene compound or a compound synthesized by any one of the methods of the second aspect, the third aspect and the fourth aspect Aza[7]helicene compounds.
[0029] As a preferred embodiment of the sixth aspect, the perovskite solar cell is composed of a substrate, a transparent oxide electrode, a hole transport layer, a perovskite photoactive layer, an electron transport layer and a metal electrode from bottom to top.
[0030] Furthermore, the electron transport layer material is preferably C60-BCP.
[0031] The present invention adopts the electrochemical synthesis method to provide The 1,1-diaza[7]helicene can be used as a hole transport material, and the prepared perovskite solar cell has high energy conversion efficiency. Experimental results show that the 1,1-diaza[7]helicene prepared by the present invention has high energy conversion efficiency. The energy conversion efficiency of perovskite solar cell devices with aza[7]helicene compounds as hole transport layers can reach up to 18.8%. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a schematic diagram of the structure of a PSC device, where the hole transport layer material is The electron transport layer material is C60-BCP and the photoactive layer is perovskite.
[0033] Figure 2 JV curve of PSC device based on PBBA7-C16 as hole transport layer. DETAILED DESCRIPTION
[0034] The present invention is further described and illustrated below in conjunction with the accompanying drawings and specific embodiments.
[0035] The present invention uses 6-amino As the starting material, the electrochemical synthesis method of electrooxidation CC, CN coupling, aromatization tandem and alkylation reaction was synthesized. Aza[7]helicene, as shown in formula I; The pyrazine fused product shown in formula II was synthesized by electrochemical method of electrooxidative CN coupling and aromatization tandem reaction using 1,2-diaza[7]helicene as raw material. The present method directly constructs nitrogen-polycyclic aromatic hydrocarbons by using polycyclic aromatic amines and electrochemical oxidation via a single electron transfer (SET) pathway, avoiding the use of catalysts and chemical oxidants, and has the advantages of high reaction selectivity, high synthesis efficiency, and environmental friendliness. In addition, compared with D-π-D type hole transport materials (HTMs), the polynitrogen-doped PAHs synthesized by the present invention without electron donors are a new type of π-conjugated mother core of HTMs.
[0036]
[0037] Wherein: R is selected from a straight chain or branched C6-C16 hydrocarbon group.
[0038] It should be noted that the above formula I shown Aza[7]helicene can be used as an intermediate to further synthesize the raw material of the compound represented by formula II - amino Therefore, 6-amino As the starting material, the pyrazine fused The overall preparation method of the aza[7]helicene compound is as follows:
[0039] First, compound 1 (6-amino ) as a raw material, and synthesizing compound 2 by the aforementioned electrochemical synthesis method; compound 2 is alkylated to obtain compound 3 (in the embodiment, it is divided into four types: 3a, 3b, 3c, and 3d according to different R groups); compound 3 is nitrated to obtain compound 4 (in the embodiment, it is divided into four types: 3a, 3b, 3c, and 3d according to different R groups), and compound 4 is reduced to obtain amino Aza[7]helicene compound 5 (in the embodiment, it is divided into four types: 3a, 3b, 3c, and 3d according to different R groups) is prepared. Compound 5 is then synthesized into a pyrazine fused The aza[7]helicene compounds (in the embodiment, they are divided into four types: 3a, 3b, 3c, and 3d according to different R groups) are prepared by the following route:
[0040] Compound 1 (6-amino ) as raw materials, synthesized Route of 3-aza[7]helicene compound:
[0041]
[0042] by Aza[7]helicene compound 3 was used as a raw material to synthesize amino Route to 1-aza[7]helicene:
[0043]
[0044] Amino Aza[7]helicene compound 5 was used as a raw material to synthesize pyrazine-fused Synthesis route of 1-aza[7]helicene compounds:
[0045]
[0046] It should be noted that in the above synthesis route, compounds 3 to 6 in the subsequent examples are divided into four types according to different R groups, but in fact the R group is not limited to these four types and can be selected from linear or branched C6 to C16 hydrocarbon groups. It is only necessary to use different raw materials in the process of alkylating compound 2 to obtain compound 3. Generally speaking, if the R group is a hydrocarbon group with a carbon number of X, it is necessary to add the raw material C in the alkylation reaction. X H 2X+1 I.
[0047] The present invention also provides a perovskite solar cell, the perovskite solar cell includes a hole transport layer, the hole transport layer is prepared by the above technical solution and is represented by formula I or formula II Aza[7]helicene compounds.
[0048] According to the present invention, the thickness of the hole transport layer is preferably
[0049] In the present invention, the device structure of the perovskite solar cell can be found in Figure 1 . Figure 1 This is a schematic diagram of the device structure of the perovskite solar cell provided by the present invention, wherein the multilayer structure includes, from bottom to top, a substrate, a transparent oxide electrode, an electron transport layer, a photoactive layer, a hole transport layer and a metal electrode.
[0050] Among them, the substrate can be any substrate well known to those skilled in the art without any special restrictions. In the present invention, glass, quartz, flexible PET or PEN are preferred. The transparent oxide electrode can be any transparent oxide electrode well known to those skilled in the art without any special restrictions. In the present invention, fluorine-doped tin oxide (FTO) or indium tin oxide (ITO) is preferred. The electron transport layer can be any electron transport layer well known to those skilled in the art without any special restrictions. In the present invention, TiO2, PC61BM, PC71BM or ZnO are preferred. The photoactive layer can be any photoactive layer well known to those skilled in the art without any special restrictions. In the present invention, the preferred chemical formula is Cs x (FA 0.83 MA 0.17 ) (1-x) Pb(Br 0.17 I 0.83) 3, where (0 < x < 0.1). The metal electrode can be a metal electrode well-known to those skilled in the art without special limitations. In the present invention, it is preferably gold, silver, magnesium, aluminum or calcium, and the thickness of the metal electrode is preferably The electron transport layer material is preferably C60-BCP.
[0051] The following examples will help to understand the present invention, but the protection scope of the present invention is not limited to the content of the following examples:
[0052] Example 1 Synthesis of Compound 2:
[0053]
[0054] In a 300 mL single-compartment electrolytic cell equipped with a Pt anode, a graphite cathode and a magnetic stirring bar, compound 1 (6-amino )(200 mg, 243.3 g / mol, 0.82 mmol), nBu4NPF6 (3.874 g, 387.43 g / mol, 0.1 M) and 100 ml of acetonitrile were added. The reaction mixture was stirred at room temperature and electrolyzed at a constant potential of 1.0 V. The reaction progress was monitored by thin-layer chromatography (DCM:PE = 2:1 v / v). After 2 hours, the reaction was completed, and 150 ml of dichloromethane was added dropwise to quench the reaction. The solution was concentrated under reduced pressure, and the residue was purified by silica gel column chromatography (DCM:PE = 2:1 v / v) to obtain 154.8 mg of a pale yellow powdery solid compound 2 (467.17 g / mol) with a yield of 80.8%. The structural characterization data of the synthesized compound 2 are as follows:
[0055] 1 1H NMR (500 MHz, THF-d8) δ 12.40 (s, 1H), 9.07 - 8.81 (m, 6H), 7.97 (d, J = 8.8 Hz, 2H), 7.80 - 7.74 (m, 6H), 7.59 (d, J = 8.4 Hz, 2H), 7.05 (dd, J = 7.4 Hz, 2H), 6.31 - 6.18 (m, 2H). 13 13C NMR (126 MHz, THF-d8) δ 132.53, 129.54, 128.88, 127.78, 126.50, 125.26, 124.31, 124.26, 123.75, 123.41, 122.65, 122.56, 122.09, 121.09, 121.04, 119.52, 118.93, 113.44. HR-MS (MALDI-TOF) m / z calcd. For (C 36 H 21N):467.1674.Found:467.1576.FT-IR:2955,2923,2853,1661,1572,1494,1461,1427,1364,1231,1155,1067,863,814,756,670.
[0056] Based on this Example 1, the parameters of the synthesis reaction can be further adjusted, so the subsequent Examples 2 to 4 are used to demonstrate different process parameter selections for synthesizing the same compound 2 as this Example.
[0057] Example 2 Synthesis of Compound 2:
[0058] Compound 1 (6-amino) was added to a 300 mL single-cell electrolytic cell equipped with a Pt anode, a graphite cathode and a stirring magnet. ) (200 mg, 243.3 g / mol, 0.82 mmol), nBu4NPF6 (3.874 g, 387.43 g / mol, 0.1 M) and 100 ml of acetonitrile were added, the reaction mixture was stirred at room temperature and electrolytically reacted at a constant potential of 2.0 V, and the reaction progress was monitored by thin layer chromatography (DCM: PE = 2: 1 v / v). The reaction was completed after 2 hours, and 150 ml of dichloromethane was added dropwise to quench the reaction. The solution was concentrated under reduced pressure, and the residue was purified by silica gel column chromatography (DCM: PE = 2: 1 v / v) to obtain 172.0 mg of light yellow powder solid compound 2 (467.17 g / mol), with a yield of 90.0%.
[0059] Example 3 Synthesis of Compound 2:
[0060] Compound 1 (6-amino) was added to a 300 mL single-cell electrolytic cell equipped with a Pt anode, a graphite cathode and a stirring magnet. ) (200 mg, 243.3 g / mol, 0.82 mmol), nBu4NPF6 (3.874 g, 387.43 g / mol, 0.1 M) and 100 ml of acetonitrile were added, the reaction mixture was stirred at room temperature and electrolytically reacted at a constant potential of 3.0 V, and the reaction progress was monitored by thin layer chromatography (DCM: PE = 2: 1 v / v). The reaction was completed after 1 hour, and 150 ml of dichloromethane was added dropwise to quench the reaction. The solution was concentrated under reduced pressure, and the residue was purified by silica gel column chromatography (DCM: PE = 2: 1 v / v) to obtain 147.2 mg of light yellow powder solid compound 2 (467.17 g / mol), with a yield of 76.9%.
[0061] Example 4 Synthesis of Compound 2:
[0062] Compound 1 (6-amino) was added to a 300 mL single-cell electrolytic cell equipped with a Pt anode, a graphite cathode and a stirring magnet. ) (200 mg, 243.3 g / mol, 0.82 mmol), 1-butyl-3-methylimidazolium tetrafluoroborate (2.26 g, 226.02 g / mol, 0.1 M) and 100 ml of acetonitrile were added, the reaction mixture was stirred at room temperature and electrolytically reacted at a constant potential of 2.0 V, and the reaction progress was monitored by thin layer chromatography (DCM: PE = 2: 1 v / v). The reaction was completed after 1 hour, and 150 ml of dichloromethane was added dropwise to quench the reaction. The solution was concentrated under reduced pressure, and the residue was purified by silica gel column chromatography (DCM: PE = 2: 1 v / v) to obtain 139.3 mg of light yellow powder solid compound 2 (467.17 g / mol), with a yield of 72.7%.
[0063] Example 5 Synthesis of Compound 3a:
[0064]
[0065] 100 mg of compound 2 (467.17 g / mol) was dissolved in 15 ml of a 1:1 mixed solvent of ultra-dry DMF and THF, and 113 mg of C6H 13 I (212.07 g / mol) and 42.8 mg NaH (60%, 24 g / mol) were stirred at room temperature for 6 hours, then the reaction solution was poured into water and extracted with DCM, the organic phase was concentrated under reduced pressure, and purified by silica gel column chromatography (Tol:PE=1:5) to obtain 109.6 mg of yellow powder solid compound 3a (551.73 g / mol), with a yield of 92.8%. The structural characterization data of the synthesized compound 3a are as follows:
[0066] 1 H NMR(500MHz, CDCl3)δ9.00(d,J=7.5,2.1Hz,2H),8.83(d,J=8.9Hz,2H),8.73-8.73(m,2H),7.95(d,J=8.8Hz,2H),7.80-7.69(m,6H),7.57- 7.56(m,2H),7.09-7.05(m,2H),6.38-6.35(m,2H),5.43-5.28(m,2H),2.06(q,J=9.4,4.3Hz,2H),1.25-1.10(m,6H),0.72(t,J=7.1Hz,3H). 13C NMR (126MHz, CDCl3) δ137.86,131.32,130.55,130.36,127.83,126.56,126.40,126.16,125.61,125.44,125.36,124.78,124 .53,123.63,122.82,120.72,117.84,77.28,77.23,77.02,76.77,51.91,31.07,29.72,26.14,22.36,13.76.HR-MS(ESI)m / z calcd.For(C 42 H 33 N):551.2613.Found:551.2612.
[0067] Example 6 Synthesis of Compound 3b:
[0068]
[0069] 100 mg of compound 2 (467.17 g / mol) was dissolved in 15 ml of a 1:1 mixed solvent of ultra-dry DMF and THF, and 153 mg of C 10 H 21 I (268.18 g / mol) and 42.8 mg NaH (60%, 24 g / mol) were stirred at room temperature for 6 hours, then the reaction solution was poured into water and extracted with DCM, the organic phase was concentrated under reduced pressure, and purified by silica gel column chromatography (Tol:PE=1:5) to obtain 121.8 mg of yellow powder solid compound 3b (607.84 g / mol), with a yield of 93.6%. The structural characterization data of the synthesized compound 3b are as follows:
[0070] 1 H NMR(500MHz, CDCl3)δ8.98(d,2H),8.82(d,2H),8.73-8.73(m,2H),7.96(d,2H),7.82-7.66(m,6H),7.56-7.57( m,2H),7.09-7.05(m,2H),6.38-6.35(m,2H),5.23-5.18(m,2H),1.74(m,2H),1.29-1.26(m,14H),0.87(t,3H). 13C NMR (126MHz, CDCl3) δ137.6,131.3,130.5,130.6,127.8,126.6,126.4,126.6,125.6,125.4 ,125.6,124.7,124.5,123.6,122.8,120.7,117.8,58.9,31.8,29.6,29.4,29.3,22.7,14.6.
[0071] Example 7 Synthesis of Compound 3c:
[0072]
[0073] 100 mg of compound 2 (467.17 g / mol) was dissolved in 15 ml of a 1:1 mixed solvent of ultra-dry DMF and THF, and 145 mg of C 12 H 25 Br (249.23 g / mol) and 42.8 mg NaH (60%, 24 g / mol) were stirred at room temperature for 12 hours, then the reaction solution was poured into water and extracted with DCM, the organic phase was concentrated under reduced pressure, and purified by silica gel column chromatography (Tol:PE=1:5) to obtain 124.6 mg of yellow powder solid compound 3c (635.90 g / mol), with a yield of 91.5%. The structural characterization data of the synthesized compound 3c are as follows:
[0074] 1 H NMR(500MHz, CDCl3)δ9.00(d,2H),8.83(d,2H),8.73-8.73(m,2H),7.95(d,J=8.8Hz,2H),7.80-7.69(m,6H),7.57-7 .56(m,2H),7.09-7.05(m,2H),6.38-6.35(m,2H),5.35-5.26(m,2H),3.06(m,1H),1.25-1.10(m,16H),0.88(m,6H). 13 C NMR (126MHz, CDCl3) δ137.9,131.3,130.5,130.6,127.8,126.6,126.4,126.2,125.6,125.4,125.6,124.8,124.5 ,123.6,122.8,120.7,117.8,77.3,77.3,77.1,76.8,51.9,34.5,32.8,32.7,29.6,29.2,27.2,23.4,22.6,14.2.
[0075] Example 8 Synthesis of Compound 3d:
[0076]
[0077] 100 mg of compound 2 (467.17 g / mol) was dissolved in 15 ml of 1:1 ultra-dry DMF and THF, 159.0 mg of C 16 H 33 I (352.16 g / mol) and 49.7 mg NaH (60%, 24 g / mol) were added to a mixed solvent and stirred at room temperature for 6 hours. The reaction solution was then poured into water and extracted with DCM. The organic phase was concentrated under reduced pressure and purified by silica gel column chromatography (Tol:PE=1:5) to obtain 139.2 mg of yellow powdery solid compound 3d (692.00 g / mol) with a yield of 93.9%. The structural characterization data of the synthesized compound 3d are as follows:
[0078] 1 HNMR (500MHz, CDCl3): δ8.97(d,2H),8.83(d,2H),8.72(d,2H),7.96(d,2H),δ7.78-7 .72(m,6H),7.09(t,2H),6.35(t,2H),5.32(m,2H),2.31(s,1H),1.07-0.19(m,30H).
[0079] 13 C NMR (126MHz, CDCl3) δ131.3,130.5,130.4,128.1,126.7,126.4,125.9,124.4123.8,123.6,123.5,120.7 118.5,56.8,56.7,31.8,31.5,31.4,31.4,29.7,29.4,29.3,29.2,29.0,28.9,22.7,22.6,22.5,22.2,14.2,14.1,14.0,13.7.
[0080] HRMS(ESI)m / z:[M+Na] + Calcd for C 52 H 53 NNa 714.4070; Found 714.4072.
[0081] Example 9 Synthesis of Compound 4a:
[0082]
[0083] 0.068 ml of 90% nitric acid was dissolved in 10 ml of chloroform, and then 1 ml of the solution was mixed with 20 ml of chloroform solution containing 100 mg of compound 3a (551.73 g / mol). The mixture was refluxed at 80°C in an oil bath for 4 hours, neutralized with an aqueous NaOH solution to a pH of 7, and then extracted with dichloromethane. The solution was concentrated under reduced pressure and purified by silica gel column chromatography (Tol:PE=1:2) to obtain 95.9 mg of a red viscous solid compound 4a (596.73 g / mol) with a yield of 88.7%. The structural characterization data of the synthesized compound 4a are as follows:
[0084] 1 HNMR (500MHz, THF-d8): δ9.47(s,1H),8.71-8.54(m,3H),8.43-8.37(m,3H),7.73-7.53(m ,6H),7.11-6.93(m,4H),6.20-6.10(m,2H),5.01(s,2H),1.85(s,1H),1.03-0.23(m,31H).
[0085] 13 CNMR (125MHz, CDCl3): δ142.7,131.2,128.2,128.2,126.6,126.5,126.0,125.9,125.7,124.6,124.5,124.2,124.0 ,122.0,120.1,60.0,56.9,31.8,31.5,31.1,29.3,29.2,29.1,29.0,28.9,22.7,22.6,22.5,22.3,14.2,14.0,13.7.
[0086] HRMS (ESI) m / z [M+H] + Calcd for [C 42 H 33 N2O2] + 597.2537; Found 597.2535
[0087] Example 10 Synthesis of Compound 4d:
[0088]
[0089] Dissolve 0.2 ml of 90% nitric acid in 5 ml of chloroform, take 1 ml of the solution and mix it with 20 ml of chloroform solution containing 139.2 mg of compound 3d (692.00 g / mol). Reflux the mixture in an oil bath at 80°C for 4 hours, neutralize it with an aqueous NaOH solution to a pH of 7, and then extract it with dichloromethane. Concentrate the solution under reduced pressure, and purify it by silica gel column chromatography (Tol:PE=1:2) to obtain 130.5 mg of red viscous solid compound 4b (736.40 g / mol), with a yield of 88.1%. The structural characterization data of the synthesized compound 4d are as follows:
[0090] 1 HNMR (500MHz, THF-d8): δ9.47(s,1H),8.71-8.54(m,3H),8.43-8.37(m,3H),7.73-7.53(m, 6H),7.11-6.93(m,4H),6.20-6.10(m,2H),5.01(s,2H),δ1.85(s,1H),1.03-0.23(m,31H).
[0091] 13 CNMR (125MHz, CDCl3): δ142.7,131.2,128.2,128.1,126.6,126.5,126.0,125.9,125.7,124.6,124.5,124.2,124.0 ,122.0,120.7,57.0,56.9,31.8,31.5,31.7,29.3,29.2,29.1,29.0,28.9,22.7,22.6,22.5,22.3,14.2,14.0,13.7.
[0092] Similarly, by replacing compound 3d in this example with the same molar amount of compounds 3b and 3c, compounds 4b and 4c can be synthesized in the same manner as compound 4d.
[0093] Example 11 Synthesis of Compound 5a:
[0094]
[0095] 671 mg of compound 4a (596.73 g / mol), 96.7 mg of 5% Pd / C and 1 ml of hydrazine hydrate were mixed in 40 ml of EtOH:THF=1:1, and the mixture was refluxed in an oil bath at 80°C for 3 hours. After the reaction was complete, the filtrate was filtered, washed with tetrahydrofuran, and the crude product was purified by flash Al2O3 column chromatography (Tol:PE=7:1) to obtain 603.0 mg of brown powder solid compound 5a (566.27 g / mol), with a yield of 94.7%, which was directly used in the next step.
[0096] Example 12 Synthesis of Compound 5d:
[0097]
[0098] 300 mg of compound 4d (736.40 g / mol), 48.5 mg of 5% Pd / C and 0.75 ml of hydrazine hydrate were mixed in 40 ml of EtOH:THF=1:1, and the mixture was refluxed in an oil bath at 80°C for 3 hours. After the reaction was completed, the filtrate was filtered, washed with tetrahydrofuran, and the crude product was purified by flash Al2O3 column chromatography (Tol:PE=7:1) to obtain 274.3 mg of brown powder solid compound 5d (706.43 g / mol) with a yield of 95.3%, which was directly used in the next step.
[0099] Similarly, by replacing compound 4d in this example with the same molar amount of compounds 4b and 4c, compounds 5b and 5c can be synthesized by the same method.
[0100] Example 13 Synthesis of Compound 6a:
[0101]
[0102] In a 300mL single-cell electrolytic cell equipped with a Pt anode, a graphite cathode and a stirring rod, compound 5a 650mg (566.27g / mol), nBu4NPF6 (3.874g, 0.1M) and 100ml acetonitrile were added. The reaction mixture was stirred and electrolyzed at a constant potential of 1.0V for 2 hours, monitored by thin layer chromatography (DCM: PE = 1: 2v / v). Then 150ml of dichloromethane was added dropwise to quench the reaction. The solution was concentrated under reduced pressure, and the residue was then purified by silica gel column chromatography (DCM: PE = 1: 2v / v) to obtain orange-red powdered solid compound 6a (1126.45g / mol) 570.5mg, with a yield of 88.2%.
[0103] The structural characterization data of the synthesized compound 6a are as follows:
[0104] HRMS (ESI) m / z [M+H] + Calcd for [C 84 H 63 N4] + 1127.5047; Found 1127.5042.
[0105] Based on Example 13, the parameters of the synthesis reaction can be further adjusted, so the subsequent Examples 14 to 16 are used to demonstrate different process parameter selections for synthesizing the same compound 6a as in this example.
[0106] Example 14 Synthesis of Compound 6a:
[0107] In a 300mL single-cell electrolytic cell equipped with a Pt anode, a graphite cathode and a stirring rod, compound 5a 650mg (566.27g / mol), nBu4NPF6 (3.874g, 0.1M) and 100ml acetonitrile were added. The reaction mixture was stirred and electrolyzed at a constant potential of 2.0V for 2 hours, monitored by thin layer chromatography (DCM: PE = 1: 2v / v). Then 150ml of dichloromethane was added dropwise to quench the reaction. The solution was concentrated under reduced pressure, and the residue was then purified by silica gel column chromatography (DCM: PE = 1: 2v / v) to obtain orange-red powdered solid compound 6a (1126.45g / mol) 602.5mg, with a yield of 93.2%.
[0108] Example 15 Synthesis of Compound 6a:
[0109] In a 300mL single-cell electrolytic cell equipped with a Pt anode, a graphite cathode and a stirring rod, compound 5a 650mg (566.27g / mol), nBu4NPF6 (3.874g, 0.1M) and 100ml acetonitrile were added. The reaction mixture was stirred and electrolyzed at a constant potential of 3.0V for 2 hours, monitored by thin layer chromatography (DCM: PE = 1: 2v / v). Then 150ml of dichloromethane was added dropwise to quench the reaction. The solution was concentrated under reduced pressure, and the residue was then purified by silica gel column chromatography (DCM: PE = 1: 2v / v) to obtain orange-red powdered solid compound 6a (1126.45g / mol) 561.3mg, with a yield of 86.8%.
[0110] Example 16 Synthesis of Compound 6a:
[0111] In a 300mL single-cell electrolytic cell equipped with a Pt anode, a graphite cathode and a stirring rod, compound 5a 650mg (566.27g / mol), 1-butyl-3-methylimidazolium tetrafluoroborate (2.26g, 0.1M) and 100ml acetonitrile were added. The reaction mixture was stirred and electrolyzed at a constant potential of 2.0V for 2 hours, monitored by thin layer chromatography (DCM: PE = 1: 2v / v). Then 150ml of dichloromethane was added dropwise to quench the reaction. The solution was concentrated under reduced pressure, and the residue was then purified by silica gel column chromatography (DCM: PE = 1: 2v / v) to obtain orange-red powder solid compound 6a (1126.45g / mol) 558.5mg, with a yield of 86.4%.
[0112] Example 17 Synthesis of Compound 6b:
[0113]
[0114] Compound 5b (255.8 mg, 622.86 g / mol), 1-butyl-3-methylimidazolium tetrafluoroborate (2.26 g, 0.1 M) and 100 ml of acetonitrile were added to a 300 mL single-cell electrolytic cell equipped with a Pt anode, a graphite cathode and a stirring magnet. The reaction mixture was stirred and electrolytically reacted at a constant potential of 2.0 V, and the reaction progress was monitored by thin layer chromatography (DCM: PE = 1: 2 v / v). After 2 hours of reaction, 150 ml of dichloromethane was added dropwise to quench the reaction. The solution was concentrated under reduced pressure, and the residue was purified by silica gel column chromatography (DCM: PE = 1: 2 v / v) to obtain 216.5 mg of orange powder solid compound 6b (1239.66 g / mol) with a yield of 85.2%. The structural characterization data of the synthesized compound 6b are as follows: HR-ESI-MS m / z calcd.For (C 92 H 78 N4):1239.6562.Found:1239.6565.
[0115] Example 18 Synthesis of Compound 6c:
[0116]
[0117] Compound 5c (234.2 mg, 659.91 g / mol), 1-butyl-3-methylimidazolium tetrafluoroborate (2.26 g, 0.1 M) and 100 ml of acetonitrile were added to a 300 mL single-cell electrolytic cell equipped with a Pt anode, a graphite cathode and a stirring magnet. The reaction mixture was stirred and electrolytically reacted at a constant potential of 2.0 V, and the reaction progress was monitored by thin layer chromatography (DCM: PE = 1: 2 v / v). After 2 hours of reaction, 150 ml of dichloromethane was added dropwise to quench the reaction. The solution was concentrated under reduced pressure, and the residue was purified by silica gel column chromatography (DCM: PE = 1: 2 v / v) to obtain 211.8 mg of orange powder solid compound 6c (1299.77 g / mol) with a yield of 91.5%. The structural characterization data of the synthesized compound 6c are as follows: HR-ESI-MS m / z calcd.For(C 94 H 86 N4):1271.7414.Found:1271.7410.
[0118] Example 19 Synthesis of Compound 6d:
[0119]
[0120] In a 300mL single-cell electrolytic cell equipped with a Pt anode, a graphite cathode and a stirring magnet, compound 5d (274.3mg, 706.43g / mol), n-Bu4NPF6 (3.874g, 387.43g / mol, 0.1M) and 100ml acetonitrile were added. The reaction mixture was stirred and electrolytically reacted at a constant potential of 2.0V, and the reaction progress was monitored by thin layer chromatography (DCM:PE=1:2v / v). After 2 hours of reaction, 150ml of dichloromethane was added dropwise to quench the reaction. The solution was concentrated under reduced pressure, and the residue was then purified by silica gel column chromatography (DCM:PE=1:2v / v) to obtain 233.5mg of orange powdered solid compound 6b (1406.81g / mol) with a yield of 85.6%. The structural characterization data of the synthesized compound 6d are as follows: 1 H NMR (500MHz, CDCl3): δ11.18(s,2H),9.32(m,2H),8.98(m,2H),8.82-8.86(m,6H),8.02-7.77 (m,16H),7.67-7.32(m,3H),7.00-6.60(m,2H),5.40(s,4H),2.25(m,2H),0.89-0.36(m,62H). 13 CNMR (126MHz, CDCl3): δ140.53,131.49,130.71,127.36,127.23,126.93,126.50,126.45,125.93,125.75,125.50,124.45, 124.22,120.77,118.37,57.35,31.65,31.45,31.23,29.07,29.02,28.94,22.56,22.45,22.25,14.00,13.92,13.86,13.61.
[0121] HR-ESI-MS m / z calcd.For(C 104 H 102 N4):1407.8182.Found:1407.8182.
[0122] Based on Example 19, the parameters of the synthesis reaction can be further adjusted, so the subsequent Examples 20 to 22 are used to demonstrate different process parameter selections for synthesizing the same compound 6d as in this example.
[0123] Example 20 Synthesis of Compound 6d:
[0124] In a 300mL single-cell electrolytic cell equipped with a Pt anode, a graphite cathode and a stirring magnet, compound 5b (274.3mg, 706.43g / mol), n-Bu4NPF6 (3.874g, 387.43g / mol, 0.1M) and 100ml acetonitrile were added. The reaction mixture was stirred and electrolytically reacted at a constant potential of 2.0V, and the reaction progress was monitored by thin layer chromatography (DCM:PE=1:2v / v). After 2 hours of reaction, 150ml of dichloromethane was added dropwise to quench the reaction. The solution was concentrated under reduced pressure, and the residue was then purified by silica gel column chromatography (DCM:PE=1:2v / v) to obtain 250.4mg of orange powdered solid compound 6b (1406.81g / mol) with a yield of 91.8%.
[0125] Example 21 Synthesis of Compound 6d:
[0126] In a 300mL single-cell electrolytic cell equipped with a Pt anode, a graphite cathode and a stirring magnet, compound 5b (274.3mg, 706.43g / mol), n-Bu4NPF6 (3.874g, 387.43g / mol, 0.1M) and 100ml acetonitrile were added. The reaction mixture was stirred and electrolytically reacted at a constant potential of 3.0V, and the reaction progress was monitored by thin layer chromatography (DCM:PE=1:2v / v). After 2 hours of reaction, 150ml of dichloromethane was added dropwise to quench the reaction. The solution was concentrated under reduced pressure, and the residue was then purified by silica gel column chromatography (DCM:PE=1:2v / v) to obtain 228.5mg of orange powdered solid compound 6b (1406.81g / mol) with a yield of 83.7%.
[0127] Example 22 Synthesis of Compound 6d:
[0128] Compound 5b (274.3 mg, 706.43 g / mol), 1-butyl-3-methylimidazolium tetrafluoroborate (2.26 g, 0.1 M) and 100 ml of acetonitrile were added to a 300 mL single-cell electrolytic cell equipped with a Pt anode, a graphite cathode and a stirring magnet. The reaction mixture was stirred and electrolytically reacted at a constant potential of 2.0 V, and the reaction progress was monitored by thin layer chromatography (DCM: PE = 1: 2 v / v). After 2 hours of reaction, 150 ml of dichloromethane was added dropwise to quench the reaction. The solution was concentrated under reduced pressure, and the residue was then purified by silica gel column chromatography (DCM: PE = 1: 2 v / v) to obtain 222.8 mg of orange powdered solid compound 6b (1406.81 g / mol) with a yield of 81.6%.
[0129] Example 23 Preparation of solar cells:
[0130] The compounds 3a, 3b, 3c, 3d, 6a, 6b, 6c, and 6d prepared in the above embodiments can all be used as hole transport layer materials for perovskite solar cells, and the perovskite solar cells prepared therefrom have high energy conversion efficiency. In order to demonstrate the specific device performance of perovskite solar cells, the following uses the compound 3a (PBBA7-C6 prepared in Example 5 and the compounds 6a (PBBA7-C6), 6b (PBBA7-C10), 6c (PBBA7-C12), and 6d (PBBA7-C16) prepared in Example 13, Example 17, Example 18, and Example 19 as examples to demonstrate the performance of perovskite solar cells based on the corresponding compounds as hole transport layers.
[0131] The process of preparing solar cell devices using PBBA7-C16 is as follows:
[0132] 1. Cleaning ITO transparent conductive glass: Select ITO transparent conductive glass with a sheet resistance of 8-15Ω, a transmittance of 80-90%, and a thickness of 2mm, and ultrasonically clean it in deionized water, ethanol, acetone, and isopropanol solutions for 5 minutes, then blow it dry with nitrogen, and then use a UV ozone cleaning machine for 15 minutes.
[0133] 2. Preparation of hole transport layer: 5 mg PBBA7-C16 and 0.1 mg F4TCNQ (2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane) as dopants were dissolved in 1 mL chlorobenzene to form a precursor solution of hole transport material. The hole transport layer was prepared by spin coating 40 uL PBBA7-C16 solution on an ITO substrate at a rotation rate of 6000 rpm for 40 s, and then annealing at 100 ° C for 10 minutes in a glove box with N2.
[0134] 3. Dissolve 214.4 mg FAI, 15.5 mg MAI, 14.6 mg CsI, 20.3 mg MACl and 645.4 mg PbI2 in 1 mL of a mixed solvent containing anhydrous DMF and DMSO (4:1 v / v). After filtration, the perovskite precursor solution was spin-coated on the PBBA7-C16 layer at 4000 rpm for 40 seconds. Chlorobenzene was added as an anti-solvent at 30 seconds into the spin coating process. The substrate was then immediately transferred to a hot plate and annealed at 105 °C for 10 minutes. 25 nm C60 and 5 nm BCP were sequentially Finally, 100 nm Ag was deposited by thermal evaporation as the electrode of the device.
[0135] Similarly, the process of preparing solar cell devices using BA7-C6, PBBA7-C10, PBBA7-C12, and PBBA7-C16 is consistent with the previous steps 1 to 3, except that PBBA7-C16 is replaced with the same molar amount of the corresponding compound.
[0136] Thus, in this embodiment, the five kinds of Five solar cell devices were prepared using the aza[7]helicene compounds PBBA7-C16, PBBA7-C12, PBBA7-C10, PBBA7-C6 and BA7-C6 as hole transport layers, and the photovoltaic performance tests were performed. The results are as follows:
[0137] Table 1 shows different Photovoltaic performance parameters of perovskite solar cell devices with aza[7]helicene compounds as hole transport layer
[0138]
[0139] #imgpt69#
[0140] in, Figure 2 The JV curve of a perovskite solar cell device based on a hole transport layer prepared with PBBA7-C16 is shown exemplarily.
[0141] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A synthesis The method for producing aza[7]helicene compound is characterized by: The amino group represented by formula VI The pyrazine fused compound shown in formula II was synthesized by electrochemical synthesis method. Aza[7]helicene compounds; Wherein: R is selected from a linear or branched C6-C16 hydrocarbon group; The electrochemical synthesis method is a series reaction consisting of electro-oxidative CN coupling and aromatization; The electrochemical synthesis method is as follows: placing the raw material in an electrolytic cell with an anode and a cathode, using nBu4NPF6 or 1-butyl-3-methylimidazolium tetrafluoroborate as a supporting electrolyte, and performing an electrochemical reaction at a constant potential of 1.0 to 3.0 V in an organic solvent; The electrolytic cell is a single-cell electrolytic cell, the anode is a Pt anode, the cathode is a graphite cathode, and the organic solvent is acetonitrile.
2. A synthesis according to claim 1 Method for synthesizing 1,2-diaza[7]helicene compounds Application of aza[7]helicene compounds as hole transport materials.
3. A perovskite solar cell, characterized in that: The hole transport layer material of the perovskite solar cell is the synthetic Method for synthesizing 1,2-diaza[7]helicene compounds Aza[7]helicene compounds.
4. The perovskite solar cell according to claim 3, characterized in that From bottom to top, perovskite solar cells are composed of a substrate, a transparent oxide electrode, a hole transport layer, a perovskite photoactive layer, an electron transport layer and a metal electrode.
Citation Information
Patent Citations
Chrysene-based aza [7] helicene compound as well as preparation method and application thereof
CN113801057A